Occurrence of Thelazia rhodesii Infection in a Jersey Crossbred Cow – A Case Report - Rangasamy, Velusamy; Annamalai, Latchumikanthan; Kanniappan, Vijayasarathi Matheri; Arunachalam, Kumaresan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Thelaziosis is a helminthic disease caused by spirurid  nematode of the genus Thelazia, which causes infection  in orbital tissues of several animals including cattle, horses,  dogs and humans worldwide (Otranto et al., 2001). Cattle  are mainly infected by Thelazia rhodesii, Thelazia gulosa, and  Thelazia skrjabini. Among these, Thelazia rhodesii is the most  common parasite affecting cattle in many countries (Otranto  et al., 2001). Horses, camels, and dogs are primarily infected by  T. lacrimalis, T. leesei and T. callipaeda, respectively. It is mainly  transmitted by secretophagous flies that feed on lacrimal  secretions such as non-biting dipteran flies of the genus  Musca (Muscidae) (Giangaspero et al., 2000). Face flies, viz., Musca autumnalis, Musca convexifrons and Musca larvipara  have been incriminated as vectors for Thelazia species  infesting cattle and horses (Giangaspero et al., 2000). The rate  of infection is high during summer and rainy seasons when the  fly population is abundant (Venkatesan et al., 2019). Clinically,  thelaziosis is considered as an important parasitic disease  because of its zoonotic nature (Otranto et al., 2007). In the  definitive hosts, the larval stages and adults cause excessive  lacrimation, epiphora, conjunctivitis, keratitis and corneal  ulcers (Deepthi and Yalavarthi, 2012). Bovine thelaziosis was  first reported in Iran by Ebadi in 1951 and other investigators  in many countries, however only limited studies are recorded  in India (Arunachalam et al., 2017; Sivajothi et al., 2023). This  case report focused on the occurrence, identification, clinical  and therapeutic management of Thelazia rhodesii infection in  a Jersey crossbred cow in central part of Tamil Nadu.
Keywords: Thelazia rhodesii, Jersey cow, Levamisole, Ivermectin, Namakkal